Assessment Methods for Service-Learning Projects in Engineering in Higher Education: A Systematic Review - Queiruga-Dios, Marián; Santos Sánchez, María Jesús; Queiruga-Dios, Miguel Ángel; Acosta Castellanos, Pedro Mauricio; Queiruga-Dios, Araceli (Frontiers in Psychology, 2021)
Service-learning helps engineering students to be involved in community activities and to be motivated by their studies. Although several papers and research studies have been published about service-learning, it is not wide spread in sciences and engineering at the university level. The purpose of this research is to analyze the different community services or projects where service-learning is implemented by engineering students and faculty, and identify the procedures that were usually implemented to assess service-learning based courses and activities. Assessment could be considered the evaluation of a specific module and the engineering competences, the evaluation of the effectiveness of the service-learning program, the assessment of student’s participation in those programs, and the assessment of whether students have achieved certain outcomes or gained specific skills. We conducted a systematic review with a search in three scientific databases: Scopus, Science Direct, and ERIC educational database to analyze the assessment methods and what that assessment covers. From 14,107 publications related to service learning, 120 documents were analyzed to inform the final conclusions of this study. We found that service-learning is widely used in several universities as experiential education, and it is considered an academic activity. The most widely used assessment technique is a survey to evaluate students’ engagement, and attitudes, and, to a lesser extent, teamwork presentations.